STUDIES ON DEMERSAL FISHES OF THE DEEP NERITIC WATERS AND THE CONTINENTAL SLOPE I. On the Stromateoid Fish Psenes indicus (Day) from the Indian Seas, wifli Comments on the Genus and Related Species and Notes on Its Biology - Silas, E G; Prasad, N K (Indian Journal of Fisheries, 2011)
IN the course of the last seven years the senior author has been able to makecollections of pelagic and bathypelagic fishes as well as neritic deep-waterfishes found more abundantly towards the edge of the continental shelf,from off the south-west coast of India during cruises of the Research VesselVARUNA and other vessels operating in association with it. These investigations,which are in progress, were taken up primarily for getting a morecomplete picture of the ichthyofauna of the area to enable proper identificationsand studies of the fish eggs and larvae of the plankton collectedduring these cruises. Diverse gear, namely, otter trawls, Isaacs-Kidd midwatertrawls, longlines, driftnets, handlines and plankton ringnets of differentsizes have been used for making the collections.